PENGARUH PENGGUNAAN APLIKASI DETEKSI ANEMIA BERBASIS ANDROID (SI-MIA) TERHADAP PERILAKU DETEKSI ANEMIA PADA IBU HAMIL DI KOTA BENGKULU - Lusi Andriani; Ratna Dewi; Silpia Novrianti (JURNAL MEDIA KESEHATAN, 2022)
Background : Basic Health Research Data (Riskesdas) in 2018, anemia that occurs in pregnant women in Indonesia is (48.9%), based on these data the incidence of anemia in pregnant women in Indonesia is still increasing and is high. Bengkulu City has 20 health centers, based on data from the Bengkulu City Health Office, the prevalence of anemia in pregnant women in 2018 was 3 health centers with the highest rates, namely Sawah Lebar Puskesmas (39.6%), Puskesmas Padang Serai (35.8%), Puskesmas Kuala Lempuing (25%). The purpose of this study was to determine the Android-Based Anemia Detection Application (Si-Mia) on anemia detection behavior in pregnant women in Bengkulu City. Method : This study used a quasi-experimental design with a control group. Collecting data used a questionnaire. The sample was 60 pregnant women who met the inclusion criteria consisting of 30 people as the intervention group and 30 as the comparison group. Data analysis used univariate, bivariate Wilcoxon and Mann Whitney tests, and multivariate using Mancova. Result : The results of the study of the knowledge variable there were differences in the mean rank before 0.00 and after 15.00, the value of p = 0.000. Attitude variables mean rank before 0.00 and after 15.50 p value = 0.000. Practice variables mean rank before 0.00 and after 15.00, p value = 0.000. There is a significant effect of the independent variable of the Android-Based Anemia Detection Application (Si-Mia) intervention on knowledge, attitudes and practices with a p value (0.000) while the covariate variable does not affect it with a p value greater than α = 0.05. Conclusion : Continuous assistance is needed to motivate pregnant women in early detection of complications during pregnancy and childbirth.